Assessment of Dysfunctional Grief due to Death from COVID-19 in Peru: Adaptation and Validation of a Spanish Version of the Pandemic Grief Scale - Caycho-Rodríguez, Tomás (2021)
ABSTRACT This study evaluated the psychometric properties of the Pandemic Grief Scale (PGS), using Classical Test Theory (CTT) and Item Response Theory (IRT) methods, in a sample of 458 people who have suffered the loss of a loved one due to the COVID-19 pandemic. The Pandemic Grief Scale, Patient Health Questionnaire-2 (PHQ-2), the two-item Generalized Anxiety Disorder Scale (GAD-2), and a single item on suicidal ideation were used. The unidimensional model had good fit and reliability; furthermore, convergent validity was demonstrated based on the relationships between dysfunctional grief, anxiety symptoms, depression, and suicidal ideation. Additionally, a higher presence of dysfunctional grief is required to answer using the higher response categories. The evidence of validity and reliability of the PGS in its Spanish version, using traditional and modern methods, is confirmed in Peru.